2011
DOI: 10.1029/2009jf001473
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of self-organized megaripples in the nearshore

Abstract: [1] Megaripples are bed forms with heights of 20-50 cm and lengths of 1-10 m that are common in the surf zone of natural beaches. They affect sediment transport, flow energy dissipation, and larger-scale hydro-and morphodynamics. They are thought to be dynamically similar to bed forms in deserts, rivers, and deeper marine environments. Here a self-organization model (similar to models for subaerial bed forms) is used to simulate the formation and development of megaripples in the surf zone. Sediment flux is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(125 reference statements)
2
10
0
Order By: Relevance
“…The megaripple domain was characterised by higher levels of turbulence than the wave ripple domain (Fig. 13) consistent with their presence under breaking waves and this supports the hypothesis proposed by Gallagher (2011), according to which megaripples appear in the surf zone following a bed perturbation, for example in the form of scour pits generated by breaking waves. Scour pits were identified on the seabed as the breaker zone passed the instruments on the ebbing tide on Day 1 and preceding the (re)appearance of megaripples.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The megaripple domain was characterised by higher levels of turbulence than the wave ripple domain (Fig. 13) consistent with their presence under breaking waves and this supports the hypothesis proposed by Gallagher (2011), according to which megaripples appear in the surf zone following a bed perturbation, for example in the form of scour pits generated by breaking waves. Scour pits were identified on the seabed as the breaker zone passed the instruments on the ebbing tide on Day 1 and preceding the (re)appearance of megaripples.…”
Section: Discussionsupporting
confidence: 85%
“…Under shoaling waves and lower bed shear stresses, wave ripples (re-)appeared. These observations support the model proposed by Gallagher (2011) according to which megaripples appear spontaneously when conditions allow, and are possibly preceded by bed perturbations in the form of scour holes formed by breaking waves. In the first few hours of their existence (i.e.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Self-organization theory suggests that nearshore bedforms including cusps, ripples and megaripples either grow or remain stable in size, depending on the forcing conditions (Clarke and Werner 2004;Gallagher 2011). Where hydrodynamic conditions do result in bedform modification, the timeframe for change may be long (Soulsby 1997), leading to the potential for the hydrodynamic conditions to be out of equilibrium with the seabed.…”
Section: Introductionmentioning
confidence: 99%
“…Self-organization based models have provided a mechanism for wavelength growth, and are able to predict both stable wavelengths and replicate growth characteristics (Coco and Murray, 2007;Gallagher, 2011). Gallagher (2011) modelled selforganized megaripples in the nearshore and found that the selforganization model of bedform spacing leads to the prediction that the megaripples will grow continually.…”
Section: Introductionmentioning
confidence: 98%